The Implementation of Zero Waste Concepts in Operational Six Senses Uluwatu, Bali - Urmila, Ni Putu Wulan Diah; Astuti, Ni Nyoman Sri; Triyuni, Ni Nyoman (Journal of Business on Hospitality and Tourism, 2022)
Waste generation in Bali has increased, it is because the waste generated is not managed properly. The impacts of this phenomenon affected climate change, such as loss of biodiversity, climate, growth of water and soil, pollution, deforestation, and waste of re-sources and materials from productive uses. The purpose of this study is to determine the implementation of the zero waste concepts in Six Senses Uluwatu, Bali. This study uses a qualitative descriptive method, conducted based on four scopes of application of the zero waste concepts; management, economic, organizational, and regulatory policy. Researchers use participatory observation, interviews, and documentation for the same data source simultaneously. This research uses the triangulation method which also tests the credibility of the data. The results of this study indicate that the implementation of zero waste concepts has reached 78 percent in accordance with company guidelines owned by Six Senses Uluwatu, Bali. The improvement of storage & separations indicators, recycle & disposal indicator, and human resources indicators on maintaining the provision of training program to the staffs are needed to carried out the waste management inside the resort. Action plans are needed to increase the percentage of zero waste concept implementation in operational at Six Senses Uluwatu, Bali which can be improved on compliance & monitoring indicators.